THE RESULTS OF THE MUNICIPAL ELECTIONS IN 2005–2015, THE KRASNOYARSK KRAI – SOCIOLOGICAL AND POLITICAL ANALYSIS - Zlotkovskij, Vladimir Il’ich; Celebrovskij, Sergej Aleksandrovich (Krasnoyarsk Science, 2016)
Article is devoted to the analysis of the municipal elections which took place in Krasnoyarsk Krai in 2005–2015. Relevance of a subject of research is caused by that important role which the local governments created following the results of local elections is played in everyday life of people. The used methods – sociological poll of the population and the analysis of documents. The following conclusions are drawn by results of the conducted researches. First, quality of life in municipalities decreases. Secondly, the regional authorities, since 2010, put process of formation and functioning of activity of local governments that allows to speak about a tendency of their nationalization under complete control. Thirdly, selective activity of the population, because of decrease in opportunities of their influence on formation of local authorities, steadily decreases that creates danger of delegitimization of local governments. Results of researches can be used during the developing and realization of regional policy for local government. Статья посвящена анализу муниципальных выборов, состоявшихся в Красноярском крае в 2005–2015 гг. Актуальность темы исследования обусловлена той важной ролью, которую органы местного самоуправления, сформированные по итогам местных выборов, играют в повседневной жизни людей. Используемые методы – социологический опрос населения и анализ документов. По результатам проведенных исследований сделаны следующие выводы. Во-первых, качество жизни в муниципальных образованиях снижается. Во-вторых, краевые власти, начиная с 2010 г., поставили под полный контроль процесс формирования и функционирование деятельности органов местного самоуправления, что позволяет говорить о тенденции их огосударствления. В-третьих, избирательная активность населения, по причине снижения возможностей их влияния на формирование местных органов власти, устойчиво снижается, что создает опасность делегитимизации органов местного самоуправления. Результаты исследований могут быть использованы при разработке и ...